ANALISIS IMPLEMENTASI MANAJEMEN PELAYANAN PUBLIK DI PUSKESMAS BANYUPUTIH - Amir, Amir; Syafi’i, Moch. (LP2M Universitas Ibrahimy, 2025)
This study aims to analyze the implementation of public service management at Banyuputih Community Health Center (Puskesmas). The main focus of the research includes planning, organizing, implementation, and supervision processes in the delivery of healthcare services. A descriptive qualitative approach was employed to obtain an in-depth understanding through observation, interviews, and documentation. The results indicate that public service management has been carried out in a relatively systematic manner, although several obstacles remain, such as limited medical personnel, inadequate facilities, and suboptimal evaluation systems. Improvement efforts are continuously being made through enhanced internal coordination and the refinement of service information systems. These findings highlight the importance of strengthening managerial functions in public services, particularly in the health sector, to improve community satisfaction and institutional performance.